Everyday life for patients with schizophrenia and severely impaired social functioning - Høier, Nanna Yosser Ben; Mølstrøm, Ida-Marie; Urfer-Parnas, Annick; Henriksen, Mads Gram; Nordgaard, Julie (Frontiers in Psychiatry, 2024)
Background: A structure of everyday life creates routines and a sense of familiarity, which provides a recognizable basis for being and acting in the world. A structure of everyday life reduces stress, and daily stress has consistently been associated with higher level of psychiatric symptoms. Little is known about how patients with schizophrenia and severe social impairment structure their lives. Thus, we aimed to explore the everyday lives of this group of patients, looking for structuring elements.Methods: In this qualitative study, we included patients diagnosed with schizophrenia who were either homeless or had difficulties reporting for treatment and, thus, needed treatment from an outreach team.Results: 17 participants were included in the study. We found only few structuring elements across all participants in the qualitative analyses. We identified five themes in our sample that serve as structuring elements in the everyday life: social interactions, volunteering to assist with basic tasks, self-initiated routines such as going for a walk daily, an exoskeleton (structure provided by others), and having pets. None of the participants reported much activity during the day, and for most of them, social interactions were minimal.Discussion: All the participants had very little structure and routines in their everyday life. The shelters provided the homeless participants with some structuring elements, whereas the domiciled participants had no external structuring elements. The findings have important implications for psychosocial treatment of severe social impairment in schizophrenia. The lack of structure in these patients' everyday lives highlights the need for targeted interventions that could facilitate such structures and guide better social involvement and personal recovery.